Analisis Perbedaan Return dan Resiko Saham dengan dan Tanpa Perataan Laba pada Perusahaan Manufaktur yang Terdaftar di BEI - Chandra, Irwan (Jurnal Akuntansi Kontemporer, 2009)
Many research proved that listed in Indonesia Stock Exchange did income smoothing. It means that management did an effort to decrease income fluctuation to reach the favorable target, whether by manipulation of artificial (by accounting method) or real (by transaction) variable. By this income smoothing they expect the risk of company will be decreased- This research is designed to know whether there are any difference between income-smoothed-company and non-income-smoothed company in their returns and/or risk. Fifty five manufacture companies, became this research samples, we selected by purposive sampling method. The samples are classified as income-smooth group and non-income-smoothed by Eckel's model. The findings showed that there is no significant difference for both stock returns and risks between income-smoothed-companies and non-income-smoothed companies. In the other words, although the income smoothing found in Indonesia but there is no difference for returns and risks variable between income-smoothed companies and non- income -smoothed-companies.